Distrust, regimes of truth, conspiracies and assemblages in the context of Covid-19 in Mexico - Murillo, Andrea (2020)
This essay examines the reproduction and circulation  of videos, images and memes for the construction of regimes of truth in the Mexican public sphere during the  Covid-19 pandemic. Since March 2020, when the circulation of information on infection rates, deaths and spikes  in cases began, through digital media and their data verification platforms, relatives of those deceased and hospitalized as a result of Covid-19 have used videos and images  on social networks to show and verify what is happening.  This accumulation of information, added to memes, generated a mood of distrust in Mexico, in the face of the different versions being shared. Based on visual methodologies, this essay examines how, through different platforms,  the image is re-appropriated and recombined with other  discursive genres during the Covid-19 pandemic in order  to achieve legitimacy and legibility. Amid an abundance  of information, the figure of the undersecretary for health,  Hugo López-Gatell, a specialist responsible for informing  Mexicans regarding the details of the pandemic, figured  prominently in efforts to disseminate figures approximating the truth. The image of López-Gatell as an emblem  of truth and national sovereignty stood in contrast to the  contradictory discourse of the current president, Andrés  Manuel López Obrador.